The Role of Sidorukun Farmers Group through the Food Security Program - Jovanca Lintang Arwana Yulianto; Hendra Sukmana (Publik : (Jurnal Ilmu Administrasi), 2026)
This study aims to describe and analyze the empowerment of the Sidorukun Farmer Group in strengthening food security in Kendalpecabean Village, Candi Sub-district, Sidoarjo Regency. The research employed a qualitative method with a descriptive approach, purposive sampling technique, and data collection through observation, interviews, and documentation. Data were analyzed using an interactive model, which includes data reduction, data display, and conclusion drawing. The theoretical framework applied is empowerment theory, which consists of five indicators: welfare, access, critical awareness, participation, and control. The findings indicate that the welfare indicator has improved through the development of irrigation channels, water gates, pumping houses, and pest control to reduce crop failure risks. The access indicator is reflected in the utilization of farmland, pumping houses, and irrigation networks, as well as efforts to stabilize grain prices and maintain solidarity among members. The critical awareness indicator emerges from farmers’ initiatives such as collective riverbank rehabilitation, simultaneous planting, and crop schedule recording. The participation indicator is seen in involvement in village meetings and planting coordination, though still largely facilitated by the government. Meanwhile, the control indicator has begun to develop through the farmer group’s organizational structure, but strategic decisions remain dependent on the village and agricultural offices. Overall, the empowerment of the farmer group has proven effective in strengthening local food security, although further improvement in participation and control aspects is needed to achieve sustainable farmer independence.